2020
DOI: 10.3389/frvir.2020.582108
|View full text |Cite
|
Sign up to set email alerts
|

Visually Induced Motion Sickness Susceptibility and Recovery Based on Four Mitigation Techniques

Abstract: Virtual reality (VR) usage continues to grow, but visually induced motion sickness (VIMS) can decrease VR effectiveness for some users. This study seeks to compare methods of VIMS mitigation and explore sickness among gender and video game experience groups. Participant discomfort and early dropout are problems for studies that involve virtual environment (VE) exposure, but previous research has demonstrated that natural decay and physical, real-world hand-eye coordination tasks can serve as effective mitigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…Researchers studying cybersickness have sought to understand its causes (Keshavarz et al, 2014;Chang et al, 2020;Stanney et al, 2020), develop measurement instruments (Davis et al, 2014;Chang et al, 2020), and identify possible mitigations (Kim et al, 2008;Nie et al, 2019;Jasper et al, 2020). However, existing research on causes of cybersickness frequently focuses on the hardware systems, e.g., latency or field of view, or on the dynamics of the imagery, e.g., with VR games rated Comfortable, Moderate, and Intense by Oculus (Fernandes and Feiner, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers studying cybersickness have sought to understand its causes (Keshavarz et al, 2014;Chang et al, 2020;Stanney et al, 2020), develop measurement instruments (Davis et al, 2014;Chang et al, 2020), and identify possible mitigations (Kim et al, 2008;Nie et al, 2019;Jasper et al, 2020). However, existing research on causes of cybersickness frequently focuses on the hardware systems, e.g., latency or field of view, or on the dynamics of the imagery, e.g., with VR games rated Comfortable, Moderate, and Intense by Oculus (Fernandes and Feiner, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, previous research has investigated how neurotypical users could mitigate motion sickness in VR, such as through the physical hand-eye-coordination tasks, real-world natural decay and adding visual effects or elements (Dennison and Krum, 2019;Jasper et al, 2020;Tian et al, 2022). However, no study tested the efficacy of these techniques for neurodivergent users.…”
Section: Discussionmentioning
confidence: 99%
“…However, as highlighted in the study by Das et al (2021), compound effects on neurodivergent users are likely to be different from the ones experienced by neurotypical users due to increased sensitivity to inducing factors. Additionally, previous research has investigated how neurotypical users could mitigate motion sickness in VR, such as through the physical hand-eye-coordination tasks, real-world natural decay and adding visual effects or elements (Dennison and Krum, 2019;Jasper et al, 2020;Tian et al, 2022). However, no study tested the efficacy of these techniques for neurodivergent users.…”
Section: Discussionmentioning
confidence: 99%
“…Experience of cybersickness and motion sickness symptoms are significantly related (Gavgani et al, 2018), suggesting that some individuals may also be highly susceptible to cybersickness symptoms, making virtual environments potentially inaccessible for certain populations. For instance, women (Jasper et al, 2020;Munafò et al, 2017), and older individuals (Arns & Cerney, 2005) have been found to be more susceptible to cybersickness, whereas those who play video games more often are less susceptible (Jasper et al, 2020). Additionally, there is some evidence for individual differences in cybersickness recovery such that women experienced a greater reduction in cybersickness symptoms in 10 minutes after discontinuation (Jasper et al, 2020).…”
Section: Individual Differences In Cybersicknessmentioning
confidence: 99%
“…For instance, women (Jasper et al, 2020;Munafò et al, 2017), and older individuals (Arns & Cerney, 2005) have been found to be more susceptible to cybersickness, whereas those who play video games more often are less susceptible (Jasper et al, 2020). Additionally, there is some evidence for individual differences in cybersickness recovery such that women experienced a greater reduction in cybersickness symptoms in 10 minutes after discontinuation (Jasper et al, 2020). Beyond demographic differences in susceptibility, understanding the role of personality in cybersickness may provide important insights due to links between personality and health (Takahashi et al, 2013).…”
Section: Individual Differences In Cybersicknessmentioning
confidence: 99%